Application of Differential Equation to Population Growth - Chaudhary, Harideo (Tribhuvan University Journal, 2013)
Thomas Malthus, an 18th century English scholar, observed an essay written in 1798 that the growth of the human population is fundamentally different from the growth of the food supply to feed that population. He wrote that the human population was growing geometrically [i.e. exponentially] while the food supply was growing arithmetically [i.e. linearly]. He concluded that left unchecked, it would only be a matter of time before the world’s population would be too large to feed itself. The first growth model we examine in this module is the one Thomas Malthus referred to in his famous essay. Malthus’ model is considered a more sophisticated model for the special case of world population.